Emotive Vocabulary as a Means of Expressing Axiological Meanings in a Hagiographic Text - Evgeniia G. Dmitrieva (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article focuses on the functional and semantic features of the vocabulary of emotions as a means of conveying ideas about spiritual and moral values, the religious and moral ideal. The research is carried out on the material of hagiographic texts of the Life of Artemy Verkolsky, which dates back to the turn of the 17th – 18th centuries. The appeal to the analysis of the lexical meaning of emotives in a synchronic anddiachronic aspect has enabled the author to identify the stability of semantic features that express two types of assessment: assessment from the position of the subject – ‘the nature of emotion’ (positive / negative / neutral) and assessment from the position of society – ‘assessment of emotional experience’ (approved / disapproved / ambivalent). It was noted that the main emotive lexemes in the Life of Artemy Verkolsky perform characterological, text-forming and didactic functions: emotives describe the significant traits of the actors, organize the compositional unity of the text and form the axiological structure of the text, convey value implications. The axiological model of the hagiographic text is constructed as an opposition of good and evil, in which heaven and earth, higher forces and man are involved, and which occurs in the human soul that is struggling with passions. The lexis of emotions expresses the key values for a Christian: attitude to God (love, fear of God) and to people (respect).